The militancy begins with joy. Public actions of children of those who suffered political repression in Córdoba and La Plata (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
Among the different actions that the Human Rights Movement developed in our country during the 1980s, workshops were held in some cities for retaliated children. These workshops were supported and promoted by the Latin American Federation of Associations of Relatives of the Detained-Disappeared (FEDEFAM). The workshops were set up as spaces in which to go through the experience of being a "son of reprisals”. The objective of this article is to analyze the cases of the "Taller Julio Cortázar" -Córdoba- and the "Taller de la Amistad" -La Plata-, taking into account the place that young people occupied in said spaces. Specifically, we are interested in studying the capacity for agency of children and adolescents who were retaliated against during State terror. We ask ourselves, what actions did the young people manage autonomously? And if these actions could be a step towards collective action in the public space? To answer both questions, in the case of Córdoba, we will focus on actions carried out by the group of adolescents from the "Taller Julio Cortázar". In them, they took over the public space or interacted with peers. In the case of La Plata, we will analyze actions and positions assumed by adolescents autonomously in said space.